Cold-formed Steel-Concrete Composite Beams with Back-to-Back Channel Sections in Bending - Andrea Rajić; Ivan Lukačević; Davor Skejić; Viorel Ungureanu (Civil Engineering Journal, 2023)
Steel-concrete composite structures are very attractive because of their characteristics, which can be emphasised by using cold-formed steel instead of hot-rolled ones. This paper presents possible analytical approaches and a parametric finite element study of cold-formed steel-concrete composite beams in bending. Analysed beams are formed of back-to-back cold-formed steel channels and concrete slabs connected by demountable shear connectors. A solid concrete slab on a profiled metal sheet analysed. Also, the study investigates the influence of corrugated web between the back-to-back channels of different thicknesses. In the case of a corrugated web, the distance between the shear connectors is increased. Furthermore, different degrees of shear connection, shear connector quality, and their arrangements are considered. An analytical study is based on full and partial shear connection assumptions and non-linear bending resistance. It is shown that the steel channel thickness and degree of shear connection significantly influence the beam bending capacity as well as concrete slab configurations. Conversely, a discrete connection between steel elements has a minor effect. A comparison of the maximum obtained bending capacities in FE analyses is in good agreement with analytical approaches for full and partial shear connections. Doi: 10.28991/CEJ-2023-09-10-01 Full Text: PDF